2020
DOI: 10.1515/jqas-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Route identification in the National Football League

Abstract: AbstractTracking data in the National Football League (NFL) is a sequence of spatial-temporal measurements that varies in length depending on the duration of the play. In this paper, we demonstrate how model-based curve clustering of observed player trajectories can be used to identify the routes run by eligible receivers on offensive passing plays. We use a Bernstein polynomial basis function to represent cluster centers, and the Expectation Maximization algorithm to learn the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The results presented are the first published description of how teams at the professional level are positioning their players during this phase of the game. The visualization in Figure 4 clearly showed that player positioning strategies varied between teams, and repeated structures or formations, were present in these data, similar to other sports [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Teams differed in their choice of player-type combinations in their forward lines at CBs ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results presented are the first published description of how teams at the professional level are positioning their players during this phase of the game. The visualization in Figure 4 clearly showed that player positioning strategies varied between teams, and repeated structures or formations, were present in these data, similar to other sports [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Teams differed in their choice of player-type combinations in their forward lines at CBs ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 66%
“…For example, it has been suggested that zone defences in AF were able to blunt the effectiveness of offensive strategies reliant on retaining ball possession [ 8 ] and that specific defensive formations in American football can reduce the offensive team’s ability to advance down the field [ 9 ]. Formations have been studied in soccer [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], American football [ 18 , 19 , 20 , 21 ], and hockey [ 22 ], reflecting the importance of formations in understanding how a sport is played. Additionally, it has been observed that soccer teams commonly switch the type of formation they use after losing a match [ 23 ], suggesting a belief among coaches that formations are a contributing factor to match outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This annual competition has similarly fueled new research directions in American football and a JQAS special issue on player tracking data in the National Football League (Lopez, 2020). Successful entries and their corresponding publications (Chu et al, 2020; Deshpande & Evans, 2020; Yurko et al, 2020) have launched the careers of several of the most prominent early‐career researchers in sports analytics.…”
Section: Opportunitiesmentioning
confidence: 99%
“…To demonstrate the usefulness of the proposed method, we present a simulation experiment and a case study from sports analytics, namely American football, a sport which has seen a steady rise in statistical analyses in recent years (see, e.g., Yam and Lopez 2019;Yurko et al 2019Yurko et al , 2020Chu et al 2020;Dutta et al 2020;Lopez 2020;Reyers and Swartz 2021). In particular, we model play calls, which can either be a run or a pass.…”
Section: Introductionmentioning
confidence: 99%